Distinctness, Uniformity and Stability Characterization of Soybean Glycine max [L.] Merrill Genotypes - Yamini Gautam; M.K. Tripathi; Riya Mishra; Jagendra Singh; D. K. Payasi; Sanjeev Sharma; Sandeep Singh Tomar; Anurag Sharma; Lalita Bishnoi (Archives of Current Research International, 2025)
Soybean is a significantly important leguminous crop known for its high protein ( 40%) and oil ( 20%) content, making it essential in human nutrition and animal feed. The current research was conducted during the Kharif, 2024 at the Zonal Agricultural Research Station, Morena, RVSKVV, Gwalior to assess qualitative characters among 60 soybean genotypes acquired from different institutions in a Randomized Block Design (RBD) with two replications. Eleven qualitative traits including hypocotyl and flower colour, leaf shape and shade, pod pubescence, growth habit, seed shape, seed coat and hilum colour and luster were recorded visually. Substantial phenotypic variation was observed. Anthocyanin pigmentation in the hypocotyl was present in 37 genotypes (61.67%); flower colour was violet in 37 (61.67%) and white in 23 genotypes (38.33%). Seed coat luster also varied where 38 genotypes (63.33%) were shiny while 22 (36.67%) were dull. Variation was also seen in leaf shape, pod surface, growth habit and hilum colour. A dendrogram was also constructed based on the qualitative traits which classified the genotypes into two primary clusters: a major contained 37 genotypes and a minor comprehend 23 genotypes. This morphological characterization provides valuable baseline information for selecting superior genotype (s) for further utilization in breeding programmes. The observed diversity can be effectively utilized for genetic improvement and conservation.